Education of Disaster Awareness through Disaster Readiness Socialization as an Effort to Increase Community Knowledge around the Nobita Hill Tourism Area on Disaster Mitigation - Marzuki Marzuki; Mutya Vonnisa; Harmadi Harmadi; Dwi Pujiastuti; Arif Budiman; Dwi Puryanti; Sri Oktamuliani; Imam Taufiq; Meqorry Yusfi; Rahmat Rasyid; Astuti Astuti; Sri Handani; Sri Rahayu Alfitri Usna; Dian Fitriyani; Elvaswer Elvaswer; Muhammad Arif; Muhammad Kahfi; Naela Amalia Zulfa; Iqbal Ramadhan; Nurul Hasanah; Feriska Handayani Irka (Warta Pengabdian Andalas, 2024)
Nobita Hill, a tourist site in Padang City, is undergoing development as a tourist destination that offers a bird's-eye view of Padang City. Unfortunately, the hilly topography with steep slopes increases the risk of landslides in this area. In order to address the problem, the community service team from the Physics Department of Andalas University has carried out a six-month community service program from July to December 2022. It focused on disaster awareness education and used a qualitative approach. This activity aims to socialize disaster mitigation efforts, especially those related to landslides and earthquakes, considering that Padang City is also prone to earthquakes. The results of this activity showed an increase in the knowledge of the local community after the socialization, but repeated activities are needed to achieve optimal results. This ongoing activity is essential to ensure continuous improvement in the community's understanding of disaster mitigation and to support efforts to make Bukit Nobita a disaster-resilient area. Thus, this activity makes a positive contribution to shaping a safe, sustainable, and disaster-resilient tourism environment.